FOREIGN LEXICAL ITEMS IN ENGLISH TEXTS AND THEIR REPRESENTATION IN UZBEK - Shaimova Fotima (TADQIQOTLAR, 2025)
Abstract: The presence of foreign lexical items in English texts reflects ongoing processes of language contact, globalization, and cultural exchange. This article examines the linguistic characteristics and functional roles of foreign words used in contemporary English texts and analyzes the strategies employed to represent these items in the Uzbek language. Foreign lexical items, including loanwords, borrowings, and code-mixed elements, often carry cultural, stylistic, and pragmatic meanings that extend beyond their denotative content. The study is based on materials drawn from literary works, media texts, and academic discourse in English, as well as their Uzbek translations. Descriptive, contrastive, and contextual analysis methods are applied to identify types of foreign lexical items and to examine translation strategies such as transliteration, transcription, calque, semantic adaptation, and functional substitution. The findings reveal that the choice of representation strategy depends on factors such as the degree of lexical assimilation in English, the cultural specificity of the foreign item, and the communicative purpose of the text. The analysis demonstrates that while transliteration and transcription are commonly used to preserve foreignness, semantic adaptation and functional equivalents are often preferred to ensure clarity and accessibility for Uzbek readers.